Rancang Bangun Aplikasi Pemesanan Dimsum Berbasis Mobile Terintegrasi dengan Virtual Account di Toko Legits - Immanuel Rivaldi; Diana Novita (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
The development of information technology has driven digital transformation across various business sectors, including Toko Legits, which still relies on manual ordering and payment systems. These processes cause several operational issues such as long queues, order recording errors, and inefficient sales data management. This study aims to design and develop a mobile-based dimsum ordering application integrated with a Virtual Account (VA) payment system to improve operational efficiency and service quality at Toko Legits. Research methods include requirement analysis through interviews and observations, system design using Unified Modeling Language (UML), mobile application implementation using Laravel and Flutter frameworks, and system testing using the black box testing method. Payment integration was implemented through the Midtrans payment gateway with a webhook mechanism for automated verification. The results indicate that the application effectively accelerates transaction processes, minimizes recording errors, and enhances data accuracy and security. A PIECES analysis confirms the superiority of the automated system over the manual system across all evaluation dimensions